A successive approximation method to precisely measure leakage current of the rechargeable Lithium coin battery. (October 2017) - Yue, X.; Kiely, J.; Ghauri, S.; Kauer, M.; Bellanger, M.; Gibson, D.
Highlights: Acquiring leakage current of Li-coin battery in μAs without electrical battery model. Observing the difference of applied current vs. leakage via a sign of voltage change. Searching trickle charge state using successive approximation. Abstract: When the rechargeable Lithium coin battery is employed as the storage component for indoor energy harvesting, the leakage current of the battery cannot be ignored, especially in ultra-low-power applications. The leakage current of the Lithium coin battery is commonly believed in the low μA range. However the exact value is unknown. An experimental method to measure leakage current by applying a known charge current in μAs to a stabilized post-charge battery to observe the sign of the battery terminal voltage change is proposed. When the applied charge current is larger than the leakage current, a positive sign (terminal voltage increase) can be observed. Otherwise a negative sign appears. By gradually changing the charge current using the successive approximation search algorithm, the leakage current will finally converge to the applied charge current. The convergence happens after the sign changes in two successive search procedures, demonstrating that charge currents are approaching the leakage current from both directions. The accuracy of the approximation can be improved by adjusting the number of sign changes in the successive approximation search algorithm. The proposed method permits the full capacity of a rechargeable Lithium coin battery to be utilised in ultra-low-power applications.